Comparing Natural Source Zone Depletion Pathways at a Fuel Release Site. Issue 2 (31st March 2018) - Mackay, Douglas; Hathaway, Emily; de Sieyes, Nicholas; Zhang, Han; Rasa, Ehsan; Paradis, Charles; Schmidt, Radomir; Peng, Juan; Buscheck, Timothy; Sihota, Natasha
Abstract: Natural source zone depletion (NSZD) refers to processes within chemically impacted vadose and saturated zones that reduce the mass of contaminants remaining in a defined source control volume. Studies of large petroleum hydrocarbon release sites have shown that the depletion rate by vapor phase migration of degradation products from the source control volume through the vadose zone (V‐NSZD) is often considerably higher than the rate of depletion from the source control volume by groundwater flow carrying dissolved petroleum hydrocarbons arising from dissolution, desorption, or back diffusion, and degradation products arising from biodegradation (GW‐NSZD). In this study, we quantified vadose zone and GW‐NSZD at a small unpaved fuel release site in California typical of those in settings with predominantly low permeability media. We estimated vadose zone using a dense network of efflux monitoring locations at four sampling events over 2 years, and GW‐NSZD using groundwater monitoring data downgradient of the source control volume in three depth intervals spanning up to 9 years. On average, vadose zone was 17 times greater than GW‐NSZD during the time interval of comparison, and vadose zone was in the range of rates quantified at other sites with petroleum hydrocarbon releases. Estimating vadose zone and GW‐NSZD rates is challenging but the vadose zone rate is the best indicator of overall source mass depletion, whereas GW‐NSZD rates may be useful as baselines to quantify progress of natural or engineered remediation in portions of the saturated zone in which there are impediments to loss of methane and other gases to the vadose zone.